Nursing students' experiences with the use of authentic assessment rubric and case approach in the clinical laboratories. (April 2015) - Wu, Xi Vivien; Heng, Mary Anne; Wang, Wenru
Summary Background One current challenge for nurse educators is to examine effective nursing assessment tools which integrate nursing knowledge into practice. Authentic assessment allows nursing students to apply knowledge to real-life experiences. Contextualized cases have engaged students for preparation of diverse clinical situations and develop critical thinking skills. Aim This study aimed to explore nursing students' experiences and learning outcomes with the use of an authentic assessment rubric and a case approach. Methods An exploratory qualitative approach using focus-group discussions and an open-ended survey was adopted. Sixteen nursing students participated in three focus-group discussions and 39 nursing students completed an open-ended survey. Results Nursing students noted that an authentic assessment rubric with a case approach provided clarity for their learning goals; built confidence; developed knowledge, skill competencies and critical thinking skills; increased awareness of caring attributes and communication skills; and enriched and extended learning through self-, peer- and teacher-assessments. Conclusions These findings provide rich insights for nurse educators and curriculum developers in the use of an authentic assessment rubric and a case approach in nursing education.